2019
DOI: 10.4269/ajtmh.18-0968
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Parasitic Infections and the Human Gut Microbiome in Odisha, India

Abstract: Soil-transmitted helminth (STH) infections and malaria are parasitic diseases with enormous global health burdens. Research has demonstrated a relationship between each of these parasites and the gut microbiome, suggesting that the gut microbiota may be implicated in governing host susceptibility to diverse pathogens, and perhaps even coinfection by different pathogens, through similar microbiome-influenced pathways. Here, we have derived a first microbiome community profile associated with STH infections in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…Our previous study also identified Lachnospiraceae as negatively associated with the three major STH infections, in human cohorts from both Liberia and Indonesia (Rosa et al, 2018). Another previous study of humans from India noted a significant negative association with Lachnospiraceae OTU and whipworm infection (Huwe et al, 2019). We confirmed a significant negative association with whipworm infection by RT-qPCR in mice (P = 0.005; Supplementary Figure S6).…”
Section: Microbiome Taxa Negatively Associated With Infectionsupporting
confidence: 82%
“…Our previous study also identified Lachnospiraceae as negatively associated with the three major STH infections, in human cohorts from both Liberia and Indonesia (Rosa et al, 2018). Another previous study of humans from India noted a significant negative association with Lachnospiraceae OTU and whipworm infection (Huwe et al, 2019). We confirmed a significant negative association with whipworm infection by RT-qPCR in mice (P = 0.005; Supplementary Figure S6).…”
Section: Microbiome Taxa Negatively Associated With Infectionsupporting
confidence: 82%
“…However, we did not find a significant difference at Pre and Post deworming, which could be because of smaller sample size and could also be confounded by the effects of albendazole. Additionally, other studies have not observed an effect of helminths on microbial diversity [8, 11, 14, 17, 18, 33]. It is important to note that each study cohort has different prevalence rates for different helminth species, as well as distinct genetics and living conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the work in this area involves describing associations between intestinal helminths and fecal samples by 16S ribosomal sequencing analysis in endemic populations. These include cross-sectional (n = 12) 53,[133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and longitudinal studies (n = 10) [148][149][150][151][152][153][154][155][156][157][158][159] , but the conclusions are often divergent, due to differences in the prevalence of helminths and study population for each analysis (see below). A common feature observed from some cross-sectional studies is increased gut microbial diversity in helminth-infected individuals 133,138,142,[144][145][146]151,153,159 ; however, some other studies showed either reduced diversity 146 or no significant differences in microbial diversity in infected individuals 134,135,139,140,143,148,…”
Section: Effects Of Helminths On Microbiome During Natural Infectionmentioning
confidence: 99%